Reading Before Writing: A Foundational Skill in AI-enhanced L2 Classrooms - Willy A. Renandya; Flora D. Floris (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2025)
This paper looks at how Artifiical Intelligence (AI) tools are changing the way writing is taught in second language classrooms. Since these tools can handle grammar and sentence structure, students can spend more time focusing on their ideas and how they communicate them. To use AI well, students need strong reading skills, especially the ability to read widely and think carefully about what they read. This paper explains why reading is now more important than ever, shares ideas from research, and gives practical tips for teachers. It also highlights the changing role of the writing teacher, who now acts more as a guide—helping students make good choices, think critically about AI output, and develop their own voice as writers.